Pemanfaatan Media Sosial dalam Proses Pembelajaran di SMPN 1 Mojo Kediri - Dina Dahniary Sholekah; Siti Wahyuni (Faculty of Tarbiyah Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
This article examines social media in learning process at SMPN 1 Mojo Kediri. This study found that the use of social media in the learning process was under the supervision and direction of the teacher. If it is outside school hours, students experience difficulties or students encounter difficulties so they can directly communicate through social media to ask questions or discuss with friends or with their teacher. The use of social media also gives a positive influence on student learning achievement. The indication is seen from the condition of students who become more enthusiastic in learning. In this way, the teacher is educating students to use social media wisely. This is one form of social media literacy socialization conducted by teachers for students Artikel ini mengkaji media sosial dalam proses pembelajaran di SMPN 1 Mojo Kediri. Penelitian ini menemukan bahwa pemanfaatan media sosial pada proses pembelajaran berada dalam pengawasan dan pengarahan dari guru. Apabila sudah di luar jam sekolah, siswa mengalami kesusahan atau siswa menemui kesulitan maka mereka bisa dengan langsung melakukan komunikasi melalui media sosial untuk bertanya atau berdiskusi dengan teman atau dengan gurunya. Pemanfaatan media sosial juga memberikan pengaruh positif pada prestasi belajar siswa. Indikasinya tampak dari kondisi siswa yang menjadi lebih bersemangat dalam belajar. Dengan cara itu, guru tengah melakukan edukasi kepada siswa untuk menggunakan sosial media secara bijak. Inilah salah satu bentuk sosialisasi literasi media sosial yang dilakukan guru untuk siswa.